Representasi Relasi Sosial pada Masa Pandemi Dalam Film Social Distance - Riyan Fredian Dzul Iftikar; Aulia Rahmawati (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
Social relations are ties of relationships or behavior between individuals. Social relations are formed differently according to the environmental conditions. The Social Distance Film Series which was produced during the Covid Pandemic makes the depiction of social relations in this film interesting, where this film is made with real-life conditions that are filled with lockdown regulations and also distance restrictions between individuals. In this study, researchers used John Fiske's semiotics research method, and collected data through documentation of scenes in the film and also literature study. Then the data will be analyzed through three levels of John Fiske's semiotics, the Reality Level, the Representation Level, and the Ideology Level. Keywords: Film Representation, Social Relation, Social Distance Film